2002
DOI: 10.1103/physrevlett.88.047601
|View full text |Cite
|
Sign up to set email alerts
|

Very-Low-Frequency Excitations in Frustrated Two-DimensionalS=12Heisenberg Antiferromagnets

Abstract: AbstractµSR and 7 Li NMR relaxation measurements in frustrated two-dimensional S = 1/2 Heisenberg antiferromagnets on a square lattice are presented. It is found that both in Li 2 VOSiO 4 and Li 2 VOGeO 4 , spin dynamics at frequencies well below the Heisenberg exchange frequency are present. These dynamics are associated with the motions of walls separating coexisting collinear domains with a magnetic wave vector rotated by 90 o . *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 16 publications
7
36
0
Order By: Relevance
“…In particular, in the prototypes of the J 1 -J 2 model, it has been observed that, similarly to what we found here, slow dynamics develop for T < J 1 + J 2 , at frequencies several orders of magnitude below k B (J 1 + J 2 )/ [15]. This has been ascribed to activated fluctuations of domain walls separating regions with (π/a,0) and (0,π/a) correlations.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In particular, in the prototypes of the J 1 -J 2 model, it has been observed that, similarly to what we found here, slow dynamics develop for T < J 1 + J 2 , at frequencies several orders of magnitude below k B (J 1 + J 2 )/ [15]. This has been ascribed to activated fluctuations of domain walls separating regions with (π/a,0) and (0,π/a) correlations.…”
Section: Discussionsupporting
confidence: 62%
“…In iron pnictides, slow fluctuations have been argued to arise from the motion of domain walls [12][13][14] that separate (π/a,0) and (0,π/a) correlated spin fluctuations, a situation analogous to that observed in frustrated vanadates [15]. The slowing down of domain wall fluctuations may be related to pinning driven by quenched disorder [7] or might be intrinsically due to underlying geometric frustration and long-range Coulomb repulsion [16].…”
Section: Introductionmentioning
confidence: 99%
“…If X is a main group (p) cation, the leading coupling is AFM J 2 , whereas J 1 is usually weaker and can be either FM (X = P) or AFM (X = Si, Ge), see also Table VII. 11,13,14 Recent efforts in crystal growth 15 and experimental investigation [16][17][18][19][20] of such compounds established the columnar AFM ground state [21][22][23] and revealed simple trends in thermodynamic properties, 15,24,25 in line with theoretical predictions.…”
Section: Introductionmentioning
confidence: 76%
“…slow and inhomogeneous) under the influence of quenched disorder or in the case of competing interactions [11]. In iron-pnictides, slow fluctuations have been argued to arise from the motion of domain walls [12][13][14] that separate (π/a, 0) and (0, π/a) correlated spin fluctuations, a situation analogous to that observed in frustrated vanadates [15]. The slowing down of domain wall fluctuations may be related to pinning driven by quenched disorder [7] or might be intrinsically due to underlying geometric frustration and long-range Coulomb repulsion [16].…”
Section: Introductionmentioning
confidence: 97%